2021
DOI: 10.1016/j.jcmgh.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Low-Density Lipoprotein Drives Dysfunction of the Liver Lymphatic System

Abstract: Chronic liver disease results in lymphatic dysfunction in the liver which can be rescued by administration of recombinant vascular endothelial growth factor C. The lymphatic dysfunction causes a decrease in lymphatic transport of molecules and occurs via oxidized LDL dependent loss of lymphatic identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
60
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 58 publications
9
60
0
Order By: Relevance
“…Because the therapeutic efficacy of ectopic administration of VEGF-C and resulting increased lymphatic drainage has been shown in mice with hepatic ischemia-reperfusion injury 6 and other diseases in different organs such as the brain, 7 lymphatic vessels and lymphatic drainage could be novel therapeutic targets for various liver diseases including NASH. The current study by Burchill et al 1 has vividly displayed this potential.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Because the therapeutic efficacy of ectopic administration of VEGF-C and resulting increased lymphatic drainage has been shown in mice with hepatic ischemia-reperfusion injury 6 and other diseases in different organs such as the brain, 7 lymphatic vessels and lymphatic drainage could be novel therapeutic targets for various liver diseases including NASH. The current study by Burchill et al 1 has vividly displayed this potential.…”
mentioning
confidence: 54%
“…In a study published in the current issue of Cellular and Molecular Gastroenterology and Hepatology , Burchill et al 1 demonstrated that alterations of LEC identity and function could lead to the development of nonalcoholic steatohepatitis (NASH). They first evaluated lymphatic vessel numbers in the livers of NASH patients with different pathologic stages and showed a positive correlation between lymphatic vessel numbers and NASH staging.…”
mentioning
confidence: 99%
“…A major challenge that limits our understanding of the progression of metabolic diseases in human is that paramount data generated on oxLDL-induced ER stress associated disorders of the liver and therapeutic targets are based on animal models. Likewise, several research groups have successfully identified targets afflicted in liver diseases that can be salvaged by pharmacological interventions, the pathological link between oxLDL and ER stress is overlooked as they are confronted from different perspectives ( Lebeaupin et al, 2018 ; Chadwick and Lajoie, 2019 ; Burchill et al, 2021 ).…”
Section: Oxidized Ldl and Er Stress In Human Diseasesmentioning
confidence: 99%
“…It was demonstrated that lymphatic vessel density was increased in the livers of NASH human subjects or NASH mice model induced by HFD [ 37 ]. Even though lymphatic vessel density was increased, the expressions of the lymphatic genes of LyECs such as podoplanin ( PDPN ), lymphatic vessel endothelial receptor-1 ( LYVE-1 ), PROX-1 , and VEGFR-3 were decreased [ 37 ]. Those changes were associated with the dedifferentiation of LyECs, which induced changes in cell-to-cell junctions and decreased lymphatic drainage [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though lymphatic vessel density was increased, the expressions of the lymphatic genes of LyECs such as podoplanin ( PDPN ), lymphatic vessel endothelial receptor-1 ( LYVE-1 ), PROX-1 , and VEGFR-3 were decreased [ 37 ]. Those changes were associated with the dedifferentiation of LyECs, which induced changes in cell-to-cell junctions and decreased lymphatic drainage [ 37 ]. The expression of VE-cadherin in the LyECs of HFD-fed mice was higher than that in control-diet-fed mice [ 37 ].…”
Section: Introductionmentioning
confidence: 99%